2021
DOI: 10.1177/10126902211038414
|View full text |Cite
|
Sign up to set email alerts
|

The grey zone between tactics and manipulation: The normalization of match-fixing in road cycling

Abstract: Match-fixing has already been studied in various sport disciplines. However, despite some well-known incidents in road cycling, match-fixing has barely been investigated in this unique sport discipline. Drawing on Ashforth and Anand’s theoretical model of normalization of corruption in organizations and on the perceptions of 15 active Belgian road cyclists, this study examines road cyclists’ attitudes towards collaboration and match-fixing in their sport. As the culture of agreements can be seen as part and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…However, the size of the sample used to arrive at these conclusions is an important limitation to their validity. Van Der Hoeven et al (2022) used a somewhat larger sample of 15 cyclists and confirmed using qualitative interviews that SRMF was indeed normalized in the sport, through three processes: institutionalization, normalization, and socialization. Yet, as was acknowledged by the authors, qualitative interviews about such sensitive topics can carry a large socially desirable nature.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…However, the size of the sample used to arrive at these conclusions is an important limitation to their validity. Van Der Hoeven et al (2022) used a somewhat larger sample of 15 cyclists and confirmed using qualitative interviews that SRMF was indeed normalized in the sport, through three processes: institutionalization, normalization, and socialization. Yet, as was acknowledged by the authors, qualitative interviews about such sensitive topics can carry a large socially desirable nature.…”
Section: Introductionmentioning
confidence: 76%
“…SRMF is a sports integrity breach and a subtype of fraud in sport that is increasingly being studied empirically in different sports (e.g. Tak et al, 2020; Van Der Hoeven et al, 2022). In this study, we aimed to reach beyond the risk factor approach to this phenomenon by experimentally manipulating six dimensions within our factorial survey's vignettes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fraud can be normalized within organizations (Ashforth & Anand, 2003). Van Der Hoeven et al (2022) describe how match-fixing is normalized in road cycling through processes of institutionalization, rationalization and socialization. Considering the highly commercialized environment sport organizations operate in (Gammelsaeter, 2021), we argue that the sport 'industry' is a crime-facilitating industry, implying the presence of structural elements which create fraud vulnerabilities (Gobert & Punch, 2003).…”
Section: Fraud Researchmentioning
confidence: 99%
“…El Convenio entró en vigor el 1 de septiembre de 2019, tras la rati cación de Grecia, Italia, Noruega, Portugal, la República de Moldavia, Suiza y Ucrania. Otros 32 estados europeos, más Australia y Marruecos (Vandercruysse et al, 2022), han rmado el convenio, aunque no lo han rati cado aún.…”
unclassified